Nilai Ekonomi Limbah Minyak Goreng Jelantah (Waste Cooking Oil) - Widiarsih, Dwi; Hadi, M.Fikry; Hidayat, Muhammad; Asnawi, Mizan; Murialti, Neng (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Community service activities with the theme of the economic value of waste cooking oil are a form of contribution to society and part of the implementation of the Tri Dharma of Higher Education of an educator (Lecturer). Waste is an environmental problem in Indonesia that will continue to be faced. One example of such waste is waste cooking oil or generally understood as waste cooking oil. Waste cooking oil is a type of waste with economic value. This type of waste can be a pollution problem, toxic and dangerous if not managed properly. The public in general has not been well educated about the negative impacts caused by waste cooking oil. People also do not understand well that waste cooking oil has economic value. The economic value of waste cooking oil can be in the form of derivative products that can be formed into ready-to-sell products such as biodiesel, aromatherapy, soap and other types of products. The results of this community service activity can be clearly measured that the participants of the event have gained an understanding, a change in attitude and a positive way of thinking about waste cooking oil, its negative impact, and how to create economic value. Keywords: Economic Value, Waste, Waste Cooking Oil